Integration Interconnection of Psychology Essence in Basics of Education and Learning - Khoirun Nisa' Auliya; Mubarok Fatahillah; Dudung Hamdun; Maksudin (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
This study aims to explain the Integration Interconnection of Psychology Essence in Basics of Education and Learning in the Arabic Language Education Class 1 of UIN Sunan Kalijaga Yogyakarta. The purpose of this study was to determine the syllabus of the Basic Education and Learning and its essence to psychology. The research method used in this research is a descriptive analytic method, while the approach used in this study is qualitative. Data collection techniques include observation, and documentation. The results that learning patterns must be carried out in an integrated manner because, psychologically, the development of cognitive abilities, socio-emotional abilities, moral abilities, and physical of students occur in an integrated and interdependent manner. Educational psychology as a science that examines mental problems and a person's psychological activity in relation to education as a process is quite important in examining problems that interfere with or support students' souls in the learning process. Teachers can organize and try to find solutions to this problem. For this matter, a teacher should have a comprehensive knowledge of educational psychology so that learning can take place effectively and directed.